2018
DOI: 10.1371/journal.pcbi.1006340
|View full text |Cite
|
Sign up to set email alerts
|

An enormous potential for niche construction through bacterial cross-feeding in a homogeneous environment

Abstract: Microorganisms modify their environment by excreting by-products of metabolism, which can create new ecological niches that can help microbial populations diversify. A striking example comes from experimental evolution of genetically identical Escherichia coli populations that are grown in a homogeneous environment with the single carbon source glucose. In such experiments, stable communities of genetically diverse cross-feeding E. coli cells readily emerge. Some cells that consume the primary carbon source gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 101 publications
1
57
0
Order By: Relevance
“…At this stage, we can only speculate what such cooperative benefits might be, but one can imagine that cells might not only differ in methionine uptake, but also in a number of other metabolic traits 21 . If so, this could allow for some form of metabolic division of labor, where subpopulations exchange metabolites in the same way as synthetic bacterial communities can exchange amino acids 8,[68][69][70][71][72] . Exploring these and other potential benefits of the long-term phenotypic heterogeneity in methionine uptake is an exciting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, we can only speculate what such cooperative benefits might be, but one can imagine that cells might not only differ in methionine uptake, but also in a number of other metabolic traits 21 . If so, this could allow for some form of metabolic division of labor, where subpopulations exchange metabolites in the same way as synthetic bacterial communities can exchange amino acids 8,[68][69][70][71][72] . Exploring these and other potential benefits of the long-term phenotypic heterogeneity in methionine uptake is an exciting topic for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Soil microbial community may also influence the determination of phyllosphere microbial diversity. However, the microbes can construct the niches in the phyllosphere microhabitat wherein it can sustain and establish its population steadily (Agler et al 2016;San Roman and Wagner 2018). Recent studies revealed the special relationships between the bacterial species in the phyllosphere community.…”
Section: Mechanism Of Microbial Interaction With the Phyllospherementioning
confidence: 99%
“…The hierarchical trophic organization suggested by our 13 model can help mechanistically establish causal links between the abundances of microbes and 14 metabolites in the human gut. 15 Introduction 16 The human gut microbiome is a complex ecosystem with several hundreds of microbial species 17 [1,2] consuming, producing and exchanging hundreds of metabolites [3,4,5,6,7]. With 18 the advent of high-throughput genomics and metabolomics techniques, it is now possible to 19 simultaneously measure the levels of individual metabolites (the fecal metabolome), as well as 20 the abundances of individual microbial species [8].…”
mentioning
confidence: 99%
“…This complexity can be tackled 32 on several distinct levels. For 2-3 species it is possible to construct a detailed dynamical model 33 taking into account the spatial organization and flow of microbes and nutrients within the lower 34 gut [13,14], or optimizing the intracellular metabolic flows as well as competition for extracellular 35 nutrients using dynamic flux balance analysis (dFBA) models [15,4].…”
mentioning
confidence: 99%